RELATIONSHIP OF EPIPHELIC DIATOMS ABUNDANCE WITH NITRATE, PHOSPHATE AND SILICATE CONCENTRATIONS IN INTERTIDAL ZONE OF WATERS KUALA TANJUNG SEI SUKA SUBDISTRICTS BATU BARA REGENCY OF NORTH SUMATERA PROVINCE - Nurhasanah Nurhasanah; Sofyan Husein Siregar; Irvina Nurrachmi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT                                                                 Diatom are microscopic plants as primary producers for most marine biota. This research has been held on March 2018 in Intertidal Zone of waters Kuala Tanjung Sei Suka Subdistrict, Batu Bara Regency, North Sumatera Province. The purpose of this study was to determine the genera epiphelic diatom abundance of Nitrate, Phosphate and Silicate concentrations and to know relationship of epiphelic diatom abundance with concentrations of Nitrate, Phosphate and Silicate. Sediment samples was taken from 4 stations and each stations was divided based on the intertidal zone (lower, middle and upper). Sample identification was obtained from 4 genera of diatom centrales and 9 genera of diatom pennales. Epiphelic diatom abundance was found in each zone ranged from 343 - 5319 ind/cm2 and at each station ranged from 686 - 6634 ind/cm2. Nitrate concentrations ranged from 0.0125 - 0.0958 mg/l, Phosphate concentrations ranged from 0.1150 - 0.8385 mg/l, and the concentration of Silicates ranged from 0.1529 - 0.3301 mg/l. Simple linear regression analysis indicates a very low negative correlation between Nitrate with abundance the epiphelic diatom, a negative correlation between Phosphate with epiphelic diatom abundance and negative correlation between Silicate with epiphelic diatom.Keyword: Intertidal Zone, Epiphelic Diatoms, Nitrate, Phosphate and Silicate